The debate and the community: 'Reflexive identity' in the FLOSS community - Francesco Rullani (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2006)
In order to simply communicate members of the Free/Open/Source Software community (FLOSS) have to negotiate the system of meanings they use to interface with the world and with the communitarian environment. But this means reshaping also their own visions of the world, redefining their identities. Community aims, principles and ethos act directly on members' identities, making them internalize the communitarian structure of rules. The first contribution of this paper is then showing how the concept of reflexivity developed by Giddens can link Wenger's idea of community of practice to developers' incentives. The result is that it is possible to find a mechanism, the reflexive identify process, acting as an antidote to free-riding and thus sustaining the cooperative production of FLOSS. However, the same mechanism shows that the community can be defined as an unstable (i.e. subject to revolutions) and dissipative (i.e. burning much more resources than the ones actually producing the outcome) object. On the theoretical side, the same mechanism asks for a wider conceptualization of practices. Using Habermas concept of 'practical interest' and 'communicative action' it is shown that the interaction between developers distributes among the different layers constituting the community debate, and that each one of these layers, not only practices, has a crucial role in defining developers' identities and thus their motivations.
Keywords: 330; Free Open Source Software; Motivation; Social Interaction; Open Source